Pola Komunikasi Melalui Fitur Virtual Pada Game Mobile Legends - Ricky Widyananda Putra (Fakultas Komunikasi & Desain Kreatif - Universitas Budi Luhur, 2023)
With the development of the human mindset and technology in the current period, in communicating not only with conventional media, but at this time in communicating can use other forms of alternative media. One of the media used in communicating is game media. With the presence of online games that use the internet network to play games, it has changed, not only as a mere entertainment medium but has changed to form a